The effect of smoking on the immediate effectiveness of induction chemotherapy in the combined treatment of HPV-associated oropharyngeal cancer - P. V. Golubev; L. V. Bolotina; A. R. Gevorkov; T. I. Deshkina (Исследования и практика в медицине)
Purpose. Evaluation of the eﬀect of smoking on the immediate eﬀectiveness (achievement of objective response – OR) of induction chemotherapy in patients receiving combined treatment for locally advanced HPV-positive squamous cell carcinoma of the oropharynx.Patients and methods. Sixty-eight patients (51 men and 17 women) with locally advanced squamous cell cancer of the oropharynx associated with papillomavirus were included in the study, which was carried out from 2021 to 2023 at the P. Hertsen Moscow Oncology Research Institute – Branch of the National Medical Research Radiological Centre, Ministry of Health of the Russian Federation, Moscow, Russian Federation and the Municipal Clinical Oncological Hospital № 1 of the Department of Health of Moscow. The patients were divided into 2 equal groups, fully comparable in terms of the main characteristics (smoking history, stage, histological type, and degree of tumour diﬀerentiation). At the ﬁrst stage, patients of the 1st (main) group received de-escalated induction chemotherapy: three 21-day courses according to the TR scheme (docetaxel in the dose of 75 mg/m2 + cisplatin 75 mg/m2); patients of the 2nd (control) group were treated with standard scheme (docetaxel 75 mg/m2 + cisplatin 75 mg/m2 + 5-ﬂuorouracil 1000 mg/m2). Patients in both groups received prophylactic granulocyte colony-stimulating factor. At the second stage, standard chemoradiotherapy was carried out against the background of drug radiomodiﬁcation with carboplatin. Correlation analysis was performed by calculating the Spearman coeﬃcient with Bonferroni correction. Diﬀerences were considered reliable at p < 0.05.Results. When evaluating the objective response to treatment, it was revealed that disease control was achieved in 33 (97 %) patients from group 1 and in all 34 (100 %) patients from group 2. Complete response was observed in 3 (8.8 %) patients from group 1 and 4 (11.8 %) from group 2; partial regression in 22 (64.7 %) and 24 (70.6 %); stabilisation of the tumour process in 8 (23.5 %) and 6 (17.6 %) respectively. Further analysis showed that there was no direct or inverse correlation between smoking and diﬀerentiated level of response (primary lesion, altered lymph nodes); all patients (smokers and those who had never smoked) responded equally eﬀectively to the ﬁrst stage of combined treatment, regardless of the ICT regimen.Conclusion. In our study, no statistically signiﬁcant eﬀect of smoking on the immediate eﬀectiveness of induction chemotherapy in the combined treatment of locally advanced HPV-associated squamous cell carcinoma of the oropharynx regardless of the induction regimen was found. However, a longer follow-up period is needed to evaluate the eﬀect of smoking on long-term oncological outcomes.